Jarosław Babiński, Ecotheology: A New Approach, Peter Lang Publishing Group, Berlin 2024, 209 s. - Kocemba, Szymon (Teologia w Polsce, 2025)
Recenzja książki: Jarosław Babiński, Ecotheology: A New Approach, Peter Lang Publishing Group, Berlin 2024, 209 s.